2017
DOI: 10.1002/cncr.30621
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in BRCA testing and cancer risk management across a population‐based sample of young breast cancer survivors

Abstract: Background Breast cancer (BC) disparities may widen with genomic advances. We compared non-Hispanic white (NHW), Black, and Hispanic BC survivors for: 1) cancer risk management practices (CRM) among BRCA carriers; and 2) provider discussion and receipt of genetic testing. Methods A population-based sample of NHW, Black, and Hispanic women diagnosed with invasive BC ≤ age 50 in 2009–2012 were recruited through the state cancer registry. Using multiple logistic regression we compared CRM in BRCA carriers and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
204
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(212 citation statements)
references
References 52 publications
5
204
3
Order By: Relevance
“…However, participants in our study reported low percentages of interpersonal encouragement from both family and providers. We and others have found that provider referral is a strong predictor of genetic counseling, but referral to genetic counseling is often low [7, 39, 40], despite national guidelines [41]. Most women in our study said their provider didn’t mention genetic counseling as an option.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, participants in our study reported low percentages of interpersonal encouragement from both family and providers. We and others have found that provider referral is a strong predictor of genetic counseling, but referral to genetic counseling is often low [7, 39, 40], despite national guidelines [41]. Most women in our study said their provider didn’t mention genetic counseling as an option.…”
Section: Discussionmentioning
confidence: 71%
“…In particular, female breast cancer survivors with a BRCA mutation have an increased risk of future cancer compared to patients without a BRCA mutation [26]. Diagnosis is the optimal time to identify, counsel, and test breast cancer patients at increased risk for hereditary cancer; however, available data suggest genetic counseling and/or genetic testing are underutilized during this time [710]. Thus, the survivorship care setting represents an important opportunity to provide genetic counseling and genetic testing for women at risk for hereditary cancer, and ultimately reduce the risk of second primary cancers in breast cancer patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…As knowledge on the genome expands, the challenges of this disease will be greater for developing countries 17 . It has been observed in the USA that fewer tests to determine BRCA1 and BRCA2 mutations are performed in Black women compared to Caucasian women, due in part to less discussion on the topic by healthcare providers 17 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…It has been observed in the USA that fewer tests to determine BRCA1 and BRCA2 mutations are performed in Black women compared to Caucasian women, due in part to less discussion on the topic by healthcare providers 17 . Given that the prevalence of BRCA mutations is higher in pre-than in postmenopausal women, the impact of disparities will be more frequently observed in the first group of women.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Population-based studies suggest that less than 60% of breast and ovarian cancer survivors at increased risk for a BRCA1/2 mutation undergo genetic testing (26). Much of our understanding of the factors associated with genetic testing decisions comes from studies of healthy at-risk individuals or cancer survivors self-referred to genetics clinics where testing uptake is high (2,7).…”
Section: Introductionmentioning
confidence: 99%